The role of SIRT1 in autophagy and drug resistance: unveiling new targets and potential biomarkers in cancer therapy - Tang, Yujing; Ju, Wantao; Liu, Yanjun; Deng, Qin (Frontiers in Pharmacology, 2024)
Cancer, the world's second leading cause of death after cardiovascular diseases, is characterized by hallmarks such as uncontrolled cell growth, metastasis, angiogenesis, hypoxia, and resistance to therapy. Autophagy, a cellular process that can both support and inhibit cancer progression, plays a critical role in cancer development and progression. This process involves the formation of autophagosomes that ultimately fuse with lysosomes to degrade cellular components. A key regulator of this process is Sirtuin 1 (SIRT1), which significantly influences autophagy. This review delves into the role of SIRT1 in modulating autophagy and its broader impacts on carcinogenesis. SIRT1 regulates crucial autophagy mediators, such as AMP-activated protein kinase (AMPK) and mammalian target of rapamycin (mTOR), effectively promoting or suppressing autophagy. Beyond its direct effects on autophagy, SIRT1's regulatory actions extend to other cell death processes, including apoptosis and ferroptosis, thereby influencing tumor cell proliferation, metastasis, and chemotherapy responses. These insights underscore the complex interplay between SIRT1 and autophagy, with significant implications for cancer therapy. Targeting SIRT1 and its associated pathways presents a promising strategy to manipulate autophagy in cancer treatment. This review underscores the potential of SIRT1 as a therapeutic target, opening new avenues for enhancing cancer treatment efficacy.